Efektivitas Pelaksanaan Pemblokiran Rekening Bank Penanggung Pajak Sebagai Upaya Penagihan Aktif di Kantor Pelayanan Pajak Pratama Serpong - Fikri Harris; Sulfan Sulfan (JURNAL PAJAK INDONESIA, 2022)
Tax is a potential state income to support the sustainability of national development. Revenue from the tax sector is state revenue with the largest percentage. The Directorate General of Taxes performs various ways to increase state revenues from the taxation sector, one of which is by collecting taxes. Effective tax collection is the right means to achieve the maximum tax revenue target. However, there is another function of tax collection, namely increasing taxpayer compliance. Blocking the tax payer's bank account is one way of collecting taxes. But in fact, even though tax collection has been carried out to the maximum, it still cannot reduce the amount of tax arrears. The purpose of this research is to find out the process of tax collection activities based on the Law on Tax Collection with Forced Letters which is the spearhead of state revenue. The method used in this study is descriptive qualitative and uses the interview method to obtain primary research data. The results of this study indicate the effectiveness and contribution of blocking actions in order to disburse tax receivables.